Meal frequencies modify the effect of common genetic variants on body mass index in adolescents of the northern Finland birth cohort 1986. - Anne Jääskeläinen; Ursula Schwab; Marjukka Kolehmainen; Marika Kaakinen; Markku J Savolainen; Philippe Froguel; Stéphane Cauchi; Marjo-Riitta Järvelin; Jaana Laitinen (PLoS ONE)
Recent studies suggest that meal frequencies influence the risk of obesity in children and adolescents. It has also been shown that multiple genetic loci predispose to obesity already in youth. However, it is unknown whether meal frequencies could modulate the association between single nucleotide polymorphisms (SNPs) and the risk of obesity. We examined the effect of two meal patterns on weekdays -5 meals including breakfast (regular) and ≤ 4 meals with or without breakfast (meal skipping) - on the genetic susceptibility to increased body mass index (BMI) in Finnish adolescents. Eight variants representing 8 early-life obesity-susceptibility loci, including FTO and MC4R, were genotyped in 2215 boys and 2449 girls aged 16 years from the population-based Northern Finland Birth Cohort 1986. A genetic risk score (GRS) was calculated for each individual by summing the number of BMI-increasing alleles across the 8 loci. Weight and height were measured and dietary data were collected using self-administered questionnaires. Among meal skippers, the difference in BMI between high-GRS and low-GRS (<8 and ≥ 8 BMI-increasing alleles) groups was 0.90 (95% CI 0.63,1.17) kg/m(2), whereas in regular eaters, this difference was 0.32 (95% CI 0.06,0.57) kg/m(2) (p interaction = 0.003). The effect of each MC4R rs17782313 risk allele on BMI in meal skippers (0.47 [95% CI 0.22,0.73] kg/m(2)) was nearly three-fold compared with regular eaters (0.18 [95% CI -0.06,0.41] kg/m(2)) (p interaction = 0.016). Further, the per-allele effect of the FTO rs1421085 was 0.24 (95% CI 0.05,0.42) kg/m(2) in regular eaters and 0.46 (95% CI 0.27,0.66) kg/m(2) in meal skippers but the interaction between FTO genotype and meal frequencies on BMI was significant only in boys (p interaction = 0.015). In summary, the regular five-meal pattern attenuated the increasing effect of common SNPs on BMI in adolescents. Considering the epidemic of obesity in youth, the promotion of regular eating may have substantial public health implications.